PENGARUH KOMUNIKASI, MOTIVASI, DAN LINGKUNGAN KERJA FISIK TERHADAP DISIPLIN KERJA KARYAWAN - Gresida, Ni Wayan Putri; Utama, I Wayan Mudiartha (E-Jurnal Manajemen; Vol 8 No 10 (2019)DO - 10.24843/EJMUNUD.2019.v08.i10.p03, 2019)
The purpose of this study is to explain the influence of communication, motivation, and physical work environment on employee work discipline. This research was conducted at the Warung Mina Peguyangan Denpasar Branch. The number of samples taken was 45 employees, with a saturated sampling method. Data collection is done through interviews and questionnaires. The analysis technique used is multiple linear regression. Based on the results of the analysis show that communication, motivation, and physical work environment have a positive and significant effect on employee work discipline. The Peguyangan Denpasar Branch Mina Warung is expected to pay more attention to fellow employees' communication, improve the health care of their employees, such as providing health insurance, and arranging rooms so that employees feel comfortable at work. Room arrangement will make it easier for employees to do work quickly, accurately, and accurately to help improve employee work discipline. Keywords: communication, motivation, physical work environment, work discipline